2019
DOI: 10.1002/ajim.23067
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to disinfectants and asthma incidence in U.S. nurses: A prospective cohort study

Abstract: Background: Exposure to disinfectants among healthcare workers has been associated with respiratory health effects, in particular, asthma. However, most studies are cross-sectional and the role of disinfectant exposures in asthma development requires longitudinal studies. We investigated the association between occupational exposure to disinfectants and incident asthma in a large cohort of U.S. female nurses. Methods: The Nurses' Health Study II is a prospective cohort of 116 429 female nurses enrolled in 1989… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 48 publications
1
39
1
Order By: Relevance
“…A cross-sectional study that included housekeepers and medical instrument cleaners found that use of various combinations of alcohol, bleach, high level disinfectants, and enzymes were associated with questionnaire-based clusters of undiagnosed asthma and asthma exacerbations [19]. In contrast, a 6-year prospective cohort study of over 60,000 nurses at a late stage of their career found no significant association between exposure to disinfectants and observed asthma incidence, but questioned whether this may have resulted from a healthy worker effect [20]. However, from another grouping drawn from the same larger cohort of female nurses, the same group found an association between questionnaire reported doctor-diagnosed chronic obstructive pulmonary disease (COPD) incidence and more frequent use of disinfectants, once a week or more [21].…”
Section: Irritant-induced Asthma (Iia)mentioning
confidence: 99%
“…A cross-sectional study that included housekeepers and medical instrument cleaners found that use of various combinations of alcohol, bleach, high level disinfectants, and enzymes were associated with questionnaire-based clusters of undiagnosed asthma and asthma exacerbations [19]. In contrast, a 6-year prospective cohort study of over 60,000 nurses at a late stage of their career found no significant association between exposure to disinfectants and observed asthma incidence, but questioned whether this may have resulted from a healthy worker effect [20]. However, from another grouping drawn from the same larger cohort of female nurses, the same group found an association between questionnaire reported doctor-diagnosed chronic obstructive pulmonary disease (COPD) incidence and more frequent use of disinfectants, once a week or more [21].…”
Section: Irritant-induced Asthma (Iia)mentioning
confidence: 99%
“…19,21 The CDC Guidelines provide good protocols for cleaning contaminated surfaces. [75][76][77] It is naturally advisable to Table 1 Different ways to reduce aerosols and droplets in dental offices 1. Abandoning and/or substituting techniques that produce droplets, if possible.…”
Section: Surface Disinfectionmentioning
confidence: 99%
“…utilize disinfectants that work on both airborne and blood born viruses and microorganisms. 77 Fogging or "Aerosol disinfection" is also an option for disinfection of surfaces without touching between the patients. There are some chemicals which can be used as vapor disinfectant including hydrogen peroxide and hypochlorous acid.…”
Section: -Gypsum Dental Modelsmentioning
confidence: 99%
See 2 more Smart Citations